Perancangan Aplikasi Pencatatan Troubleshooting Projects Berbasis Mobile Di PT. Nutech Integrasi - Syamsu Hidayat (Program Studi Teknik Informatika, Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2020)
The problems in PT. Nutech Integration, especially for technicians who work on troubleshooting, especially in terms of recording every user disturbance report on computer devices, computer applications and also data access either via the internet or with intranet access. In terms of recording each troubleshooting report, they still use a conservative way, namely using a book to record each report. With the development of information technology, especially mobile device technology, especially with the Android operating system, the author provides a solution in terms of recording every report from a user received by technicians, by creating an android application that the technicians can understand and run the application in recording each troubleshooting report.